Measuring Operational Management Information Technology: COBIT 5.0 and Capability Level - Kelvin Chandra; Wella Wella (IJNMT (International Journal of New Media Technology), 2017)
Abstrack—Every system need to be well organized so it can achieve what the company expected. So, very company need to do some measurement to create a well organize system. A type of action that can be used for creating a well organize system is quantify their IT governance PT XYZ is a company that engaged in property business. Their company want to measure their IT governance, to measured their IT governance framework COBIT 5.0 was use and as what the company request process that being measure are Manage Service Agreements, Manage Change, Manage Operations, and Manage Service Request and Incidents. Every process have their own importance and will be measured based on framework COBIT 5.0 capabilitylevel. Capability level have 5 kind of stage. PT XYZ expectation that they can achieved level 4. But, the esult that came out doesn’t match what their company has expected, the result was level 3 and on of their process stop at level 2. So, to attain the level that PT XYZ wanted they need to some improvement based on COBIT 5.0 recommendation. Index Terms—Capability Level, COBIT 5.0, Information System, IT Governance. REFERENCES [1] S. Tata, “Sistem Informasi Manajemen,” Yogyakarta, Andi, 2005. [2] R. Weber, “Information System Control and Audit,” Prentice Hall, New Jersey, 1999. [3] Kompas. http://tekno.kompas.com. 24 Agustus 2016. [4] BCA.http://www.bca.co.id/id/TentangBCA/Korporasi/Siaran-Pers/2016/02/09/04/48/Terapkan-ISO9001-2008. 25 Agustus 2016. [5] ISACA, http://www.isaca.org/. 23 August 2016. [6] Gondodiyoto et al., “Pengolahan Fungsi Audit Sistem Informasi,” Penerbit Mitra Wacana Media, Jakarta, 2007. [7] E. J. Hunton, “Core Concept of Information Technology Auditing,” New Jersey, John Willey and Sons Inc, 2004.